DEVELOPMENT OF PAPER-BASED COLOR TEST-STRIP FOR PARACETAMOL DETECTION IN JAMU - Triswanto Sentat; Henny Nurhasnawati; Yunita Rachma Dwinand (Jurnal Ilmu Kesehatan, 2019)
Chemical medicine which are synthetic chemicals or isolation products must not be added to herbal medicine, that was standared by Indonesian Head of the Drug and Food Control Agency in statement regarding Criteria and Procedure for Registration of Traditional Medicines, Standardized Herbal Medicines, and Phytofarmaka. This study aims to develope prototype of paper-based color test-strip to identify paracetamol trace in several types of Indonesian herbal medicine, better known as Jamu. Research conducted with experimental research wich make paper test-strip prototype by immobilizing reagents into Whatman’s filter paper, then it used to identify paracetamol in extracted Jamu samples. The paracetamol qualitative test uses 10 Jamu samples that distributed in Samarinda area. were also carried out on. Comparison methode with qualitative color reaction tests using specific reagents in the laboratory were also carried out beside the paper-based color test-strip methode. In addition with positive control tests using 5000 ppm paracetamol solution to make sure both methode used are valid. The results of this study showed that two prototype paper-based color test-strips containing 10% iron (III) chloride reagent and folin ciocalteu were able to detect the presence of paracetamol chemicals in Jamu samples with color reaction.